“Every Creature of God is Good”: A Lexico-Syntactical and Theological Analyses of 1 Timothy 4:1-5 - Baidoo, Elijah (Fakultas Filsafat Universitas Advent Indonesia, 2024)
False teaching in the Ephesian Church was alarming. The tone of 1 Timothy 4:1–5 shows Paul's seriousness about these false teachings, which could ruin his Ephesus ministry. Paul stated that the Holy Spirit gives end-time deception warnings. The nature of the false teachings has puzzled Paul's readers. The study investigates the nature of the false teaching, the use of βρωμα, and Paul's meaning of ὅτι πᾶv κτίσμα θεοῦ καλὸν. Paul's handling of the Ephesian church's false teaching has also been analyzed in modern Christianity. The following key difficulties were addressed through lexico-syntactical and theological study.The study concludes that the erroneous doctrine was asceticism, which posited that the material world was evil and excessive engagement with it could jeopardize one's salvation. In the Ephesian church, this doctrine was situated in a setting where certain members believed that marriage or the consumption of food could impede salvation. Consequently, they adopted fasting and celibacy as methods for attaining salvation. They asserted that self–restraint was the most reliable means of achieving salvation. According to Paul, the truth, as the gospel of Christ, which false teachers forsook, remains the reliable path to salvation. Paul teaches that God created everything for a purpose; thus food and marriage should be gratefully accepted and followed according to the Bible. Paul does not say in the verse that clean and unclean meat are no longer distinguished in Christianity. To stay truthful, scripture must guide our doctrines and practices.